Metronidazole: A culprit to balance and speech (Indian Journal of Case Reports, 2024)
In a country like India, oral metronidazole is the commonly prescribed drug of choice for entities such as amebiasis and visceral abscesses. Oral such cases, it is usually well tolerated and safe but can cause serious neurological adverse events. Peripheral neuropathy commonly encounters in practice but central nervous system toxicity is also well documented as it crosses the blood–brain barrier easily. Neurological toxicity of metronidazole may be due to prolonged administration, high doses, or high cumulative doses. Magnetic resonance imaging (MRI) of brain is the modality of choice to evaluate brain involvement. In the brain, the splenium of the corpus callosum, dentate nucleus of the cerebellum, and posterior pons involvement are commonly seen and diagnostic. Here, we have an interesting case report of a patient who was on oral metronidazole treatment for his large liver abscess, presenting with a complaint of neurological symptoms of unsteady gait, vertigo, dysdiadochokinesia, and difficulty in speech. Moreover, thus suspected as metronidazole drug toxicity and further investigated for the same, and MRI typically shows cerebellar and posterior corpus callosal involvement.